Non‐random accumulation of LINE1‐like sequences on differentiated snake W chromosomes. (5th June 2016) - Mezzasalma, M.; Visone, V.; Petraccioli, A.; Odierna, G.; Capriglione, T.; Guarino, F. M.
Abstract: Due to their particular phylogenetic position and biological characteristics, squamate reptiles and, in particular, snakes are becoming an increasingly important model for fields such as evolutionary biology, molecular ecology and adaptation. Recently, during a study to analyze the evolutionary history of European whip snakes, we found a LINE1 (L1)‐like sequence (GenBank accession no.LM644476 ), herein called TRL1L, and while there are data on the abundance of L1 in snakes, their genomic and chromosome localization is still largely unexplored. We therefore performed a study to obtain information on TRL1L abundance, distribution and conservation in snake species, belonging to the Colubridae, Lamprophiidae and Viperidae families, using quantitative dot‐blot and fluorescence in situ hybridization (FISH). TRL1L showed a high identity with homologous segments of L1s of lizards the Anolis carolinensis and Lacerta agilis and the zebrafish Danio rerio . The discovered sequences are truncated L1 elements which occur with a low copy number, about 0.1% of the genome of the species studied. This evidence suggests that L1 retroposons have a similar landscape in lizard and snake genomes, probably because similar processes limited L1 distribution in their genomes. TRL1L showed a non‐random chromosome distribution pattern. It was scarcely located on autosomes and on the euchromatic W chromosome of Cerastes vipera, while mostly found on the heterochromatic W chromosome of Hierophis carbonarius and Elaphe quatuorlineata . Our data support the hypothesis that a 'purifying selection' against the accumulation of L1 elements takes place in recombining regions and highlight the possible role of these elements in the differentiation processes of the snake heterochromatic W chromosome. Interestingly, the preferential distribution of TRL1L on the heterochromatic W chromosomes of the studied snakes appears to be similar to that observed in mammals for L1 accumulation on differentiated Y chromosomes. This finding suggests that a convergent process may have taken place in the differentiation of vertebrate heterochromatic sex chromosomes. Abstract : This study provides evidence of the scarce presence and the recent origin of LINE1 sequences in squamate genomes, and evidence a non‐random, preferential accumulation of these sequences in highly heterochromatic W sex chromosomes. Our data also highlight a similar, convergent, distribution pattern of L1 retroposons on vertebrate sex chromosomes when their differentiation takes place through heterochromatinization events.